AN ANALYSIS OF STUDENT’S READING COMPREHENSION THROUGH STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQUE - Tauricha Icha Astiyandha; Afifi Umar (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
This study consisted of two variables, namely the independent variable (STAD Technics) and the dependent variable (Reading Comprehension). The purpose of this study was to determine the usefulness of STAD on reading comprehension of class XI students at SMA Attaqwa 03 Bekasi. In addition, this research was conducted using qualitative data with a descriptive analysis approach. The subjects of this study were students of class XI SMA Attaqwa 03 in the 2020/2021 academic year, totaling 5 random students. Data collection was carried out through observation and interviews as instruments. The data analysis technique in this research is thematic analysis through answers to interview questions and then transcripts to get the topics that will be used as themes. The themes used were analyzed as a result of this study. Based on these data, the results showed that STAD can be used as a learning technique and improve students' reading comprehension. In addition, STAD can also be used by teachers as an effective learning technique to support teaching and learning activities.